PERSEPSI EFEKTIVITAS KINERJA PENYULUHTERHADAP KELOMPOKTANI DI KECAMATAN TAPUNGKABUPATEN KAMPAR - Roito, Christina Uli; Rosnita, Rosnita; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to describe the implementation of agricultural extension in Tapung district Kampar regency, analyze performance of agriculture extensionÂ  in Tapung district Kampar regency, analyze the effectiveness of the extension performance in Tapung district Kampar regency. The methods of collecting sample using Purposive Sampling and Slovin, the samples taken in this research are the group of existing districts in Tapung district which can represent beginner, advanced, and related group classes with 40 numbers of samples and this research uses a qualitative descriptive method to explain the circumstances that occur in the field. The results of this research show that the agricultural extension performance in Tapung district is relatively high with an average score of 3.99, the effectiveness of extension performance in Tapung district is also effective with an average score of 4.11.Â Keywords :Farmers, Extension Agent, the performance, and Effectiveness